Influence of injection molding parameters on electrical resistivity of carbon nanotube reinforced polycarbonate - KENTLİ, AYKUT (WALTER DE GRUYTER GMBH, 2016)
Electrical properties of plastic products can be adjusted by adding a certain amount of carbon nanotubes (CNT) in the injection molding process. However, injection molding parameters should be arranged carefully due to their influence on electrical properties of CNT-reinforced plastic composites. In this study, polycarbonate/CNT nanocomposites, having three different CNT concentrations (1, 3 and 5 wt%), were produced and injection molded by using three different injection temperatures and speeds to investigate their influence on electrical resistivity. It was found that the electrical resistivity was influenced greatly by the injection temperature when 1 wt% amount of CNT was used in the nanocomposite. However, the effect of injection speed was negligible.
Keywords: carbon nanotubes; electrical resistivity; injection molding; nanocomposites; thermoplastics; IMPACT